Tuneable Control of Organocatalytic Activity through Host–Guest Chemistry. (7th May 2021) - Li, Guotai; Trausel, Fanny; van der Helm, Michelle P.; Klemm, Benjamin; Brevé, Tobias G.; van Rossum, Susan A. P.; Hartono, Muhamad; Gerlings, Harm H. P. J.; Lovrak, Matija; van Esch, Jan H.; Eelkema, Rienk
Abstract: Dynamic regulation of chemical reactivity is important in many complex chemical reaction networks, such as cascade reactions and signal transduction processes. Signal responsive catalysts could play a crucial role in regulating these reaction pathways. Recently, supramolecular encapsulation was reported to regulate the activities of artificial catalysts. We present a host‐guest chemistry strategy to modulate the activity of commercially available synthetic organocatalysts. The molecular container cucurbit[7]uril was successfully applied to change the activity of four different organocatalysts and one initiator, enabling up‐ or down‐regulation of the reaction rates of four different classes of chemical reactions. In most cases CB[7] encapsulation results in catalyst inhibition, however in one case catalyst activation by binding to CB[7] was observed. The mechanism behind this unexpected behavior was explored by NMR binding studies and p K a measurements. The catalytic activity can be instantaneously switched during operation, by addition of either supramolecular host or competitive binding molecules, and the reaction rate can be predicted with a kinetic model. Overall, this signal responsive system proves a promising tool to control catalytic activity. Abstract : Binding an organocatalyst inside a cucurbituril molecular host can reversibly up‐ or downregulate catalytic activity, which is demonstrated in temporal control over the rate of a range of organocatalyzed transformations.